Meneladani Spiritualitas Kerendahan Hati Yesus Lewat Salib dan Kalvari: (Perspektif Armada Riyanto Dasar Filsafat Remah dan Daun Kering) - Nikodemus, Nikodemus; Andreas Jimmy (International Forum of Researchers and Lecturers, 2024)
This research study has a theological aim of the meaning of Spirituality of Humility in a Christian context experiencing a crisis of faith. The background to the writing is the author's observation of several phenomena in the practical life of Christians in modern times which are experiencing degradation, such as lack of willingness, sacrifice, humility, love and faith. The problems experienced by the author believe are due to problems with Christian spirituality in modern times. The author observes the fact that modern humans do not appreciate the events of the cross and calvary (Jesus). This experience provides the principles of spirituality, crumbs and dry leaves, which can answer the problems of modern times. The spirituality of humility brings humans to become friends of Jesus. The author uses descriptive and bibliographic analysis methods. The author conducted a theological study of the meaning of spiritual humility from Eko Armada Riyanto's book